Rede de colaboração entre bibliotecas da UNIPAMPA para o compartilhamento de materiais em formato digital acessível para usuários com deficiência visual – uma proposta de implantação - Araújo, Cátia Rosana Lemos de (2019)
This master’s thesis is linked to the Educational Technologies Network Management line of research of the Professional Master Degree from the Graduate Program in Networked Educational Technologies of the Federal University of Santa Maria – UFSM, RS. The current study addresses the access of information for the visually impaired in the libraries of the Federal University of Pampa – Unipampa, RS, with the goal of promoting informational accessibility discussion and to propose the creation of a collaboration network between libraries for sharing accessible digital materials for visually impaired users. This research is a study case, with a qualitative and applied approach and a descriptive focus. Its developed was based from a theoretical framework and current legislation pertinent to the theme. For the data collection, an online questionnaire with questions related to the accessibility and collaboration in libraries was used, in order to identify the need for implementing a collaboration network. Semi-structured interviews with visually impaired students and members of the university staff were also conducted, in order to analyze how is the access of information inside the institution; and for the results’ analysis it was used, as a guiding, the Content Analysis of Bardin (2016), approaching the categories accessibility, autonomy and accessible collections. Among the results, it was verified that the libraries and the institution are in need of accessibility actions and there are few accessible bibliographical materials to serve visually impaired students; the university needs accessible environments and functionalities to all, as a way to promote autonomy; and the participants of this research consider that it is essential for libraries to have materials in accessible formats. In conclusion, it was found that Unipampa needs affirmative policies related to accessibility matters and training of staff to assist people with disability, as well as resources to acquire accessible collections and also training, and a mindset change in order to have more interest in knowing and promoting accessibility in the institution. The urgency of implementing a collaboration network in the University for the development and sharing of digital materials in accessible format as a way to promote a greater informational accessibility for the visually impaired students was evidenced. As a product of this master’s thesis, it was developed a proposal for implementing a collaboration network between libraries from Unipampa for the creation of an accessible repository through the replication of the institutional repository (Dspace).